HUMAN RESOURCE MANAGEMENT TECHNIQUES AND JOB PERFORMANCE OF TEACHERS’ IN SPECIAL NEED SCHOOLS IN CALABAR MUNICIPALITY OF CROSS RIVER STATE, NIGERIA - Edut Egbe Obona, Udang, Joseph Akor, Egwu Umet Egeh, (EPRA International Journal of Environmental Economics, Commerce and Educational Management (ECEM), 2023)
Teacher’s performance is one crucial issue in human resource management with very strong relationship to education. Their job performance makes great contribution to the achievement of educational goals. This study examined human resource management techniques and Job performance of teachers in special need schools in Calabar municipality of Cross River State, Nigeria. To achieve this aim, three null hypotheses were formulated to guide the study. Census technique was adopted in selecting the entire population of 60 teachers. The Human Resource Management Techniques and Teachers’ Job Performance in Special Need Schools Questionnaire (HRMTTJPSNSQ) was used to elicit information for the study. The instrument was validated by experts while the reliability of the instrument was established through the Cronbach Alpha method and it ranged from .71 - .85. The null hypothesis was tested at .05 level of significance using Simple Linear Regression analysis with the aid of IBM SPSS. Findings from the study revealed that discipline, motivation and supervision techniques significantly predicted Job performance of teachers in special need schools. It was concluded generally that; human resource management techniques when combined, do significantly predict the job performance of teachers in special need schools in special need schools in Calabar municipality of Cross River State, Nigeria. Based on the findings of this study, it was recommended among other things that: Principals should ensure that erring teachers are properly disciplined to instill seriousness in others and to create an orderly school atmosphere. principals should be quick to recorgnize, compensate, reward and remunerate teachers outstanding performances in other to motivate the workforce to greater productivity; supervision of teachers should be intensified to enhance their job performance.